2019
DOI: 10.1155/2019/3862098
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Practices of HIV Positive Mothers and Its Association with Counseling and HIV Disclosure Status in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Introduction. Breastfeeding is the ideal food source for all newborns globally. However, in the era of Human Immune Deficiency Virus (HIV) infection, feeding practice is a challenge due to mother-to-child HIV transmission. Therefore, this systematic review and meta-analysis aimed to estimate the national prevalence of exclusive breastfeeding and mixed feeding practices among HIV positive mothers and its association with counseling and HIV disclosure status to the spouse in Ethiopia. Methods. We searched all av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 45 publications
(72 reference statements)
6
18
1
Order By: Relevance
“…The proportion of HIV-positive women practicing MIF was found to be 21.6%. The figure is comparable with the findings of the studies done in Addis Ababa-23.3% [24] and a systematic review and meta-analysis finding of Ethiopian pooled prevalence-23.11% [13].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The proportion of HIV-positive women practicing MIF was found to be 21.6%. The figure is comparable with the findings of the studies done in Addis Ababa-23.3% [24] and a systematic review and meta-analysis finding of Ethiopian pooled prevalence-23.11% [13].…”
Section: Discussionsupporting
confidence: 88%
“…This significant association conversely entails that infant feeding counseling (i.e., counseling on PMTCT) during ANC visit has a positive role on the appropriate infant feeding practice as it is observed in the current study that almost all (98.7%) of ANC attendees had received PMTCT counseling. This implication is further supported by existing evidences which show a positive correlation between infant feeding counseling during antenatal care and exclusive infant feeding practice [13,25,40].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Several studies have shown low rates of exclusive breastfeeding among HEI [ 6 , 11 , 12 , 14 15 16 ]. Risk factors for these low rates are not well understood and vary with in different contexts.…”
Section: Introductionmentioning
confidence: 99%